INITIATIVES OF BERLIN AMBASSADOR KEMALETTIN SAMI PASHA WHO ON TRACK TO ESTABLISH NATIONAL AVIATION: AN EXAMPLE OF JUNKERS AIRCRAFT FACTORY - Bolat, Mahmut; Öztürk, Yasin (Uluslararası Tarih Araştırmaları Dergisi, 2022)
One of the development moves after the proclamation of the republic of Turkey was tried to be realized in the field of air industry and it was aimed to establish a National Air Industry. Since the current technological and economic situation of Turkey at that time was not sufficient to create such an industry, this deficiency was tried to be eliminated by cooperation with advanced countries at this point.Germany has also been the preferred country in this regard. The relations with Germany, which were cut off after the First World War, were officially established again in the Republican period and it was aimed to benefit from the experience of Germany in the air industry. In this direction, the delegation sent to Germany reached an agreement with Germany's Junkers Aircraft Factory in 1925 with the initiatives of the Berlin Ambassador of the time Kemalettin Sami (Gökçen) Pasha, and as a result of the partnership established with Junkers, “Aircraft and Motor Turkish Joint Stock Company (TOMTAS)” was established at the same time, Kayseri Aircraft Factory was established in 1926. On the other hand, the economic bottleneck that the Junkers company entered as a result of its investments in Russia during this period prevented the activities of the aircraft factory and the factory was closed in 1928 as a result of the disagreements arising from it.In this study, Turkey's national efforts in this direction with the firm Junkers German air force of creating an industry partnership and joint venture activities and results; qualitative research methods with the method of document analysis and audit-related archival documents written using copyright works. Türkiye’de cumhuriyetin ilanı sonrası kalkınma hamlelerinden birisi de hava harp sanayii alanında gerçekleştirilmeye çalışılmış ve Millî Hava Harp Sanayii kurmak hedeflenmiştir. O dönemde Türkiye’nin mevcut teknolojik ve ekonomik durumu böyle bir sanayii oluşturmaya yeterli olmadığından bu eksiklik bu noktada ileri ülkelerle iş birliği ile giderilmeye ...